Biodegradable Nanofibrous Polymeric Substrates for Generating Elastic and Flexible Electronics. (19th July 2014) - Najafabadi, Alireza Hassani; Tamayol, Ali; Annabi, Nasim; Ochoa, Manuel; Mostafalu, Pooria; Akbari, Mohsen; Nikkhah, Mehdi; Rahimi, Rahim; Dokmeci, Mehmet R.; Sonkusale, Sameer; Ziaie, Babak; Khademhosseini, Ali
<x xml:space="preserve">Abstract</x> Biodegradable nanofibrous polymeric substrates are used to fabricate suturable, elastic, and flexible electronics and sensors. The fibrous microstructure of the substrate makes it permeable to gas and liquid and facilitates the patterning process. As a proof‐of‐principle, temperature and strain sensors are fabricated on this elastic substrate and tested in vitro. The proposed system can be implemented in the field of bioresorbable electronics and the emerging area of smart wound dressings. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>